2018
DOI: 10.1016/j.ijnss.2018.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Development of an empowerment model for burnout syndrome and quality of nursing work life in Indonesia

Abstract: Objectives This study aimed to develop an empowerment model for burnout syndrome and quality of nursing work life (QNWL). Methods This study adopted a mixed-method cross-sectional approach. The variables included structural empowerment, psychological empowerment, burnout syndrome and QNWL. The population consisted of nurses who have civil servant status in one of the regional hospitals in Indonesia. The participants were recruited using multi-stage sampling measures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 18 publications
3
47
0
8
Order By: Relevance
“…In the work world dimension, the respondents of the current study think that society has a negative image of nurses, that they do not receive adequate salary in comparison to the job market and their job impacts the lives of patients/families. The findings of this study are consistent with study (Karimi-Shahanjarini et al, 2019;Nursalam, Fibriansari, et al, 2018b) which emphasized that people think of nurses as assistants to the physicians, and many physicians also regard nurses only as their helpers and do not consider them as specialists in the art of caring. Furthermore, nurses felt that poor public image of nursing may affect not only their recruitment, but also their attitudes towards work ( Gunawan, Aungsuroch, Sukarna, & Efendi, 2018;Kaur Pushpinder & Rawat, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In the work world dimension, the respondents of the current study think that society has a negative image of nurses, that they do not receive adequate salary in comparison to the job market and their job impacts the lives of patients/families. The findings of this study are consistent with study (Karimi-Shahanjarini et al, 2019;Nursalam, Fibriansari, et al, 2018b) which emphasized that people think of nurses as assistants to the physicians, and many physicians also regard nurses only as their helpers and do not consider them as specialists in the art of caring. Furthermore, nurses felt that poor public image of nursing may affect not only their recruitment, but also their attitudes towards work ( Gunawan, Aungsuroch, Sukarna, & Efendi, 2018;Kaur Pushpinder & Rawat, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In the United States, Casida et al (2018) have confirmed the negative relationship between nurse practitioners' burnout and QoWL. Similarly, Nursalam et al (2018) have reported that burnout has an adverse effect on the QoWL of nurses in Indonesia. Job burnout is deemed to be an important influencing factor of QoWL.…”
Section: Introductionmentioning
confidence: 90%
“…Burnout could be a major factor in affecting nurses' quality of working life. Recently, although a growing number of studies have focused on nurses' job burnout or quality of working life, research on their association is still limited (Casida, Combs, Schroeder, & Johnson, 2018;Larson, Cothran, Drandorff, Morgan, & Ryan, 2012;Nursalam et al, 2018).…”
mentioning
confidence: 99%
“…Faktor-faktor yang mempengaruhi kualitas tidur lansia yang adalah stress psikologis, gizi, lingkungan, motivasi, gaya hidup dan olahraga (Nursalam et al, 2018). Lingkungan adalah faktor penting untuk penerapan sleep hygiene.…”
Section: Pendahuluanunclassified